Transcriptome analysis of xa5-mediated resistance to bacterial leaf streak in rice (Oryza sativa L.) - Xie, Xiaofang (Sci Rep, 2020)
Bacterial leaf steak (BLS) caused by Xanthomonas oryzae pv. oryzicola (Xoc) is a devastating disease in rice production. The resistance to BLS in rice is a quantitatively inherited trait, of which the molecular mechanism is still unclear. It has been proved that xa5, a recessive bacterial blast resistance gene, is the most possible candidate gene of the QTL qBlsr5a for BLS resistance. To study the molecular mechanism of xa5 function in BLS resistance, we created transgenic lines with RNAi of Xa5 (LOC_Os05g01710) and used RNA-seq to analyze the transcriptomes of a Xa5-RNAi line and the wild-type line at 9 h after inoculation with Xoc, with the mock inoculation as control. We found that Xa5-RNAi could (1) increase the resistance to BLS as expected from xa5; (2) alter (mainly up-regulate) the expression of hundreds of genes, most of which were related to disease resistance; and (3) greatly enhance the response of thousands of genes to Xoc infection, especially of the genes involved in cell death pathways. The results suggest that xa5 is the cause of BLS-resistance of QTL qBlsr5a and it displays BLS resistance effect probably mainly because of the enhanced response of the cell death-related genes to Xoc infection.